2013
DOI: 10.1371/journal.pntd.0002444
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of the Epidemiology of Leprosy in Cebu: An Eleven-Year Profile

Abstract: BackgroundCebu has been one of the most leprosy endemic areas in the Philippines. Despite the high coverage rates of multiple drug therapy (MDT) and high BCG-vaccine coverage in children, leprosy control authorities believe that leprosy transmission and incidence (as evidence by continuing new case detection in both adults and children) have not declined as expected, once leprosy had been eliminated.In response to the concerns communicated by the authorities regarding ongoing leprosy transmission in Cebu, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 11 publications
0
15
0
9
Order By: Relevance
“…In fact, this study showed the overlapping of the clusters in both periods temporally separated in ten years, which reinforces the idea of temporal and geographic persistence of the indicators of the analyzed condition. Other authors have shown the persistence of the geographic distribution of leprosy and its spatial concentration 7,8,10,16,[22][23][24] . For example, the clusters identified for the incidence rate of leprosy and for the incidence rate in adolescents aged less than 15 years are in areas similar to those mentioned in previous studies 7,10,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this study showed the overlapping of the clusters in both periods temporally separated in ten years, which reinforces the idea of temporal and geographic persistence of the indicators of the analyzed condition. Other authors have shown the persistence of the geographic distribution of leprosy and its spatial concentration 7,8,10,16,[22][23][24] . For example, the clusters identified for the incidence rate of leprosy and for the incidence rate in adolescents aged less than 15 years are in areas similar to those mentioned in previous studies 7,10,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The model with the Poisson distribution was used. This model is based on a number of events (cases of leprosy) distributed according to a known population at risk 16,17 . The statistical significance was evaluated considering p ≤ 0.05 (likelihood ratio test).…”
Section: Methodsmentioning
confidence: 99%
“…Tampouco podem ser esperadas mudanças súbitas na sua ocorrência, como por exemplo, redução da incidência 4,6,17 .…”
Section: Aspectos éTicosunclassified
“…Despite efforts to reduce the prevalence of the disease, these actions have apparently little effect on the reducing transmission and incidence [46]. Use of leprosy prevalence as an indicator has been criticized since it is influenced by factors such as treatment duration and case identification.…”
Section: Introductionmentioning
confidence: 99%